On the field leakage of the leapfrog ADI-FDTD method for nonpenetrable targets - Gan, Theng Huat (2014)
This letter investigates the field leakage of the leapfrog alternating-direction-implicit finite-difference time-domain (ADI-FDTD) method for nonpenetrable targets. The update equation for lossy media using time-averaging scheme is reviewed. Investigation reveals that the leapfrog ADI-FDTD method has substantial nonphysical field leakage within the target. To overcome the field leakage, a simple approach is proposed. Numerical results are presented to validate the proposed approach.